DISCOURSE IN THE DIGITAL AGE ([S.l.])
1 online resource
Keywords: This collection makes the case for existing critical discourse analysis theory and methods to meaningfully engage with the communicative parameters, power dynamics, and technological affordances of contemporary digital spaces. This book lends a critical focus on discursive practices operating through the paradigm of social media communication, addressing the crucial interface of discourse and the participatory web with disciplinary rigour and a well-balanced focus. This volume features chapters highlighting a diverse range of methods, including multi-sited ethnography, multimodality, argumentation studies, and topic modelling, as applied to a global range of case studies to present a holistic portrait of the latest methodological and theoretical debates in this space. The collection demonstrates the many and pervasive impacts of digital mediation on established discursive practices that are (re-)shaping existing social values, practices, and demands. In so doing, the collection advocates for a new tradition in critical discourse research, one which is rigorous in accounting for both solid discursive frameworks and the evolving complexity of digital platforms, and which triangulates methodologies in order to fully make sense of contemporary discursive practices and power relations on the online-offline continuum. This collection will be of interest to students and scholars in critical discourse studies, digital communication, media studies, and anthropology.